Economic development strategy, openness and rural poverty: A framework and China's experiences - Justin Yifu Lin; Peilin Liu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper argues that both openness and poverty in a country are endogenously determined by the country's long-term economic development strategy. Development strategies can be broadly divided into two mutually exclusive groups: (i) the comparative advantage-defying (CAD) strategy, which attempts to encourage firms to deviate from the economy's existing comparative advantages in their entry into an industry or choice of technology; and (ii) the comparative advantage-following (CAF) strategy, which attempts to facilitate the firms' entry into an industry or choice of technology according to the economy's existing comparative advantages. To carry out a CAD strategy, many governments of LDCs subsidize the firms in priority sectors by distorting capital prices, foreign exchange, and other inputs; and use administrative methods to allocate price-distorted inputs to the firms. The functions of market will be suppressed. Rent-seeking will be widespread. As a result, economic performance will be poor and the income distribution issue will worsen. Foreign trade will also be retarded. Only if governments of less-developed countries make following their economy's comparative advantage the basic principle for promoting the economy's industrial development, will the economy have an open and well functioning market, maintain a high rate of capital accumulation, upgrade its endowment structure quickly, and see a more equitable distribution of income and fewer poor.
Keywords: O14; O20; O33; N65; 330; economic development strategy; income distribution; globalization; poverty; Entwicklungsstrategie; Armut; Globalisierung; China